The Pan London Emergency Cardiac Surgery service: Coordinating a response to the COVID‐19 pandemic. Issue 7 (29th June 2020) - Hussain, Azhar; Balmforth, Damian; Yates, Martin; Lopez‐Marco, Ana; Rathwell, Claire; Lambourne, Jonathan; Roberts, Neil; Lall, Kulvinder; Edmondson, Stephen; ,
Abstract: Over the last 4 months, the novel coronavirus, SARS‐CoV‐2, has caused a significant economic, political, and public health impact on a global scale. The natural history of the disease and surge in the need for invasive ventilation has required the provision of intensive care beds in London to be reallocated. NHS England have proposed the formation of a Pan‐London Emergency Cardiac surgery (PLECS) service to provide urgent and emergency cardiac surgery for the whole of London. In this initial report, we outline our experience of setting up and delivering a pan‐regional service for the delivery of urgent and emergency cardiac surgery with a focus on maintaining a COVID‐free in‐hospital environment. In doing so, we hope that other regions can use this as a starting point in developing their own region‐specific pathways if the spread of coronavirus necessitates similar measures be put in place across the United Kingdom.